تركيب الغطاء البيدولوجي (الترابي) في المنطقة الساحلية السورية - رقيه عادل (Latakia University Journal -Biological Sciences Series, 2019)
من خلال دراستنا لتركيب الغطاء البيدولوجي (الترابي) في المنطقة الساحلية السورية وجدنا السمة المميزة له أنه غطاء معقد ويعتمد في خواصه على مادة الأصل، حيث لم يستطع المناخ المتوسطي فرض سيطرته عليها، وذلك بسبب الانجراف الشديد والمستمر تحت تأثير التضاريس الجبلية شديدة الانحدار، وهذا ما يفسر سبب سيادة الترب حديثة التكوين Entisol في تركيب الغطاء البيدولوجي في المنطقة الساحلية . تناولت الدراسة قطاعات ترب في المنطقة الرطبة ونصف الرطبة وتحت أغطية نباتية مختلفة وعلى صخور أم متنوعة وتضاريس مختلفة أيضا. هذا ما أثر على عمق الترب وخواصها ومحتواها من القطع الصخرية وعلى الرتبة التصنيفية. من الناحية التصنيفية وجدنا الترب الأكثر انتشارا تتبع للرتب التالية:الـ Entisol(الترب حديثة التكوين) الـ Mollisol( ترب ذات أفق سطحي موليك)، الـ Vertisol( الترب عميقة التشقق)، الـ Inceptisol ( الترب ضعيفة التطور )، الـ Alfisol ( ترب الغابات المشبعة). كما أظهرت الدراسة أن قطاعات ترب الغطاء البيدولوجي من النوع:A–AC–C ، A –(B)–C،A– Bt – C . Through the study of structure of pedologic cover in the coastal region of Syria, we realized that the most significant character of this cover is the complication structure; its components are mostly very dependent on the parent material; where the Mediterranean climate has no significant influence on that structure. Because of the strong and continued erosion under the influence of very accentuated relief and that explain the predominance of the Entisol in the pedologic cover of coastal region of Syria. This study investigate soil profiles for humid and semi – humid regions under different plant covers over different parent materials and topography. These variations influenced greatly soil depth, characters and content of rock fragments, and finally soil classification order. From the classification point of view we found that the most common soils can be classified in several orders like: Entisol, Mollisol, Vertisol, Inceptisol and Alfisol. The study reveals that the profiles of soils of pedologic covers are: A-AC-C, A-(B)-C and A-Bt-C.